PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PADA INDUSTRI MAKANAN DAN MINUMAN - Yanti, Adelia Islami; Diantini, Ni Nyoman Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022DO - 10.24843/EEB.2022.v11.i07.p12, 2022)
This study aims to examine the effect of firm size, collateral, profitability, and growth opportunity (independent variable) on capital structure (dependent variable) listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling with the number of samples obtained as many as 195 samples from 39 food and beverage companies listed on the IDX for the period 2016-2020. The type of this research is quantitative research, the analytical method of this research is a descriptive method and multiple analysis methods using secondary data types in the form of financial reports obtained from the website www.idx.co.id . The results of this study reveal that simultaneously firm size, collateral, profitability, and growth opportunity variables have a significant effect on capital structure variables proxied by Debt to Equity Ratio (DER). Partially, the firm size variable has no significant effect on the capital structure variable, the collateral variable has a significant negative effect on the capital structure variable, the profitability variable has a significant negative effect on the capital structure variable and the growth opportunity variable has no significant effect on the capital structure variable